The Genomic Potentials of NOB and Comammox Nitrospira in River Sediment Are Impacted by Native Freshwater Mussels - Black, Ellen M.; Just, Craig L. (Frontiers in Microbiology, 2018)
Freshwater mussel assemblages of the Upper Mississippi River (UMR) sequester tons of ammonia- and urea-based biodeposits each day and aerate sediment through burrowing activities, thus creating a unique niche for nitrogen (N) cycling microorganisms. This study explored how mussels impact the abundance of N-cycling species with an emphasis on Candidatus Nitrospira inopinata, the first microorganism known to completely oxidize ammonia (comammox) to nitrate. This study used metagenomic shotgun sequencing of genomic DNA to compare nitrogen cycling species in sediment under a well-established mussel assemblage and in nearby sediment without mussels. Metagenomic reads were aligned to the prokaryotic RefSeq non-redundant protein database using BLASTx, taxonomic binning was performed using the weighted lowest common ancestor algorithm, and protein-coding genes were categorized by metabolic function using the SEED subsystem. Linear discriminant analysis (LDA) effect sizes were used to determine which metagenomes and metabolic features explained the most differences between the mussel habitat sediment and sediment without mussels. Of the N-cycling species deemed differentially abundant, Nitrospira moscoviensis and “Candidatus Nitrospira inopinata” were responsible for creating a distinctive N-cycling microbiome in the mussel habitat sediment. Further investigation revealed that comammox Nitrospira had a large metabolic potential to degrade mussel biodeposits, as evidenced the top ten percent of protein-coding genes including the cytochrome c-type biogenesis protein required for hydroxylamine oxidation, ammonia monooxygenase, and urea decomposition SEED subsystems. Genetic marker analysis of these two Nitrospira taxons suggested that N. moscoviensis was most impacted by diverse carbon metabolic processes while “Candidatus Nitrospira inopinata” was most distinguished by multidrug efflux proteins (AcrB), NiFe hydrogenase (HypF) used in hydrogen oxidation and sulfur reduction coupled reactions, and a heme chaperone (CcmE). Furthermore, our research suggests that comammox and NOB Nitrospira likely coexisted by utilizing mixotrophic metabolisms. For example, “Candidatus Nitrospira inopinata” had the largest potentials for ammonia oxidation, nitrite reduction with NirK, and hydrogen oxidation, while NOB Nitrospira had the greatest potential for nitrite oxidation, and nitrate reduction possibly coupled with formate oxidation. Overall, our results suggest that this mussel habitat sediment harbors a niche for NOB and comammox Nitrospira, and ultimately impacts N-cycling in backwaters of the UMR.